1983
DOI: 10.1080/02705060.1983.9664601
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Macroinvertebrates of Selected Habitats of the Lower Mississippi River

Abstract: We investigated the distribution of benthic macroinvertebrates in four aquatic habitat types in the lower Mississippi River: dike fields, a natural bank, a secondary channel, and an abandoned channel over a high flow (flood stage), two moderate, and two low flow periods. The biotas present in the natural bank, the secondary channel, and the abandoned channel showed only minor changes in composition over the various flow regimes. The natural bank was consistently dominated by the burrowing mayflies Tortopus inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Sorting efficiency for 16.9 cm with smaller clams burrowing deeper mayflies and fingernail clams in the field was than larger clams (Gale 1971(Gale , 1973(Gale , 1976), thus, consistent over time (P = 0.2395 and P = 0.0733; the vast majority of target taxa fall within the respectively). These results emphasize the reach of a standard Ponar.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sorting efficiency for 16.9 cm with smaller clams burrowing deeper mayflies and fingernail clams in the field was than larger clams (Gale 1971(Gale , 1973(Gale , 1976), thus, consistent over time (P = 0.2395 and P = 0.0733; the vast majority of target taxa fall within the respectively). These results emphasize the reach of a standard Ponar.…”
Section: Introductionmentioning
confidence: 92%
“…the macroinvertebrate component was dropped Beckett et al (1983) found dike fields important from the minimum sustainable program. Future.…”
Section: Ltrmp Resource Managers Are Concerned With the Abundance Ofmentioning
confidence: 99%
“…This association appeared to include the Hydropsychidae, Bivalvia, Chironomidae, and Heptageniidae, all of which are major components of the invertebrate community of large rivers (Beckett and Miller, 1982;Beckett et al, 1983;Delong and Payne, 1985), and zooplankton. Direct or indirect consumption of dissolved organic matter by aquatic invertebrates has been well documented (Richardson and Mackay, 1991;Porter, 1996;Ciborowski et al, 1997).…”
Section: Consumer Lmentioning
confidence: 98%
“…In the Main River no clear relationship appeared bet ween depth and macroinvertebrates (Schleuter & Tittizer 1988). For Beckett et al (1983) in the Mississippi River, the macrodistribution is influenced mainly by both substrate and current velocity. Current influences macrodistribution in lowlands streams while substrate particle size and food supply are the most important factors influencing microdistribution (Tolkamp 1982, Cummins & Lauff 1969.…”
Section: What Habitat Variables Influence the Microdis Tribution Pattmentioning
confidence: 99%